2007
DOI: 10.1007/s11749-006-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic normality of the Nadaraya–Watson semivariogram estimators

Abstract: Asymptotic normality, Intrinsic stationarity, Isotropy, Kernel, Random process, Variogram, 62G05, 62G10,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Estimator is the indicator version of the kernel variogram analyzed in García‐Soidán () and involves a weighted average. The consistency of trueγ̂IYMathClass-punc,h(normaltMathClass-punc,x) can be proved and, additionally, its bias and variance can be approximated.…”
Section: Resultsmentioning
confidence: 99%
“…Estimator is the indicator version of the kernel variogram analyzed in García‐Soidán () and involves a weighted average. The consistency of trueγ̂IYMathClass-punc,h(normaltMathClass-punc,x) can be proved and, additionally, its bias and variance can be approximated.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, λ n can be determined by the diameter of a sampling region for use here (cf. García-Soidán [12], Hall and Patil [14], Maity and Sherman [23], Matsuda and Yajima [24]). Let Z = {0, ±1, ±2, .…”
Section: Preliminariesmentioning
confidence: 98%
“…To fit the variogram model in a way that allows nonparametric confidence intervals (CIs) to access the precision of the estimated parameters, without making assumptions about the joint distribution of the data or the distribution of spatial locations, one can apply the SFDEL method using estimating functions as in Example 3 motivated by least squares estimation. Alternatively, one can apply a kernel bandwidth estimator of the varigoram for which large sample distributional results are recently known (García-Soidán [12], Maity and Sherman [23]).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, simulations (not included) indicated a bandwidth of w = 0.65 maintains nominal size when n = 950, but leads to deflated test size and power when n = 400 on a smaller domain. García-Soidán et al (2004), García-Soidán (2007), and Kim and Park (2012) develop theoretically optimal bandwidths for nonparametric semivariogram estimation, but these works are not applicable here because they focus on the isotropic case and require an estimate of the second derivative of the variogram. We have found that the empirical bandwidth used by MS tends to produce nominal size (see Table 6).…”
Section: Recommendationsmentioning
confidence: 99%